Pengaruh Kemampuan Analisis Kuantitatif dan Penguasaan Statistika terhadap Pengambilan Keputusan Manajerial pada Mahasiswa Prodi Manajemen Mahasiswa di Bekasi - Wanda Ragilita Azzahro; Laili Nur Maulinasari; Muhammad Kosim; Ika Puspita; Rizky Aulia Putri Aisyah; Kiki Mustingatun (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of quantitative analysis skills and statistical mastery on managerial decision-making among Management students in Bekasi. The background of this study is based on the importance of data literacy and analytical skills in supporting effective decision-making processes, especially amidst the increasing demand for data-driven businesses. This study used a quantitative approach with a census technique on 67 respondents. Data were collected through questionnaires and analyzed using multiple linear regression through classical assumption tests, partial tests (t-tests), and simultaneous (F-tests). The results showed that both quantitative analysis skills and statistical mastery have a positive and significant effect individually on managerial decision-making skills. Quantitative analysis skills, which include the ability to process data in numerical form and interpret it critically, have been shown to strengthen decision-making skills in various situations. Likewise, statistical mastery provides a foundation for analyzing data systematically and producing evidence-based decisions. Simultaneously, these two variables explain 60.8% of the variation in decision-making. These findings emphasize the importance of mastering quantitative and statistical skills for students in facing the complexity of decision-making in a professional environment. This study recommends strengthening the curriculum and providing practical data-based training to improve students' readiness for more informed and analytically sound managerial decision-making. Furthermore, it is recommended that students be given more opportunities to engage in case studies involving real-world data, as well as the use of statistical software that can accelerate the analysis and decision-making process. Improving data and statistical literacy will give students a competitive advantage in an increasingly data-driven business world.